Universal Child Benefit and Child Poverty: The Role of Fertility Adjustments - Jan Gromadzki (Institute of Labor Economics (IZA), 2024)
I study fertility adjustments after the introduction of a large universal child benefit in Poland. The program caused a six percent increase in the number of births. Patterns of selection into parenthood changed significantly and persistently, with a weakening of positive selection based on education and a strengthening of negative selection based on income. The share of births in the bottom half of the income distribution increased from 51 percent to 58 percent. Using a microsimulation approach, I combine changes in the births structure with existing estimates of the transfer's effect on labor supply to study the impact of these adjustments on poverty reduction. These impacts are very small due to the exceptional generosity of the transfer, but they become more pronounced in the middle of the income distribution.
Keywords: J13; H31; I38; 330; fertility; child benefit; unconditional cash transfer; poverty